Environment Impact Assesment for Four Laning of Nh-64 from Zirakpur to Patiala - Sharma, Ashish (My University, 2012)
The Environmental Impact Assessment (EIA) is a systematic investigation of both positive and negative impacts on the physical, biological socioeconomic environment, which would be caused or induced due to a proposed developmental project. EIA helps to develop environmental friendly projects and seeks to reduce environmental degradation caused by developmental activities. It also provides a plan to reduce the negative environmental effects of proposed development project through alternative approaches, design modifications and remedial measures .Highway construction is a major activity of economic development especially in developing countries. Road development is major source of damage to the environment, including ecological destabilization, habitat disturbance and damage to flora and fauna. The present report analyses the environmental impacts likely to occur due to the proposed widening of a 50 km stretch of NH-64 from Zirakpur to Patiala. The report highlights the importance of EIA in the sustainable development of highway project with a case study of vital link of about 50 Kilometers. The study concentrates on the environment impact assessment of the project in the light of the existing situation at the site. The parameters covered in study are Socio-Economic, Biological, Air (Dust), Water, Noise, Ecological & Soil. Samples of air, water & soil were taken to analyze their present conditions. Data was also collected from various Government offices like the forest department and town & country planning department . The results demonstrated that the fluoride content exceeded the prescribed limits in most of the groundwater samples, PM 2.5 concentrations at all locations also exceeded the prescribed limits. Noise levels were found within permissible limits. Minimal soil contamination was observed. Highway capacity was analyzed and it was observed that the present two lane highway is insufficient to handle the current traffic volume so the section requires four laning immediately to accommodate more traffic. After analyzing different parameters and discussing the probable impacts suggestions are made regarding the mitigation measures that can be taken at different stages in order to reduce the environmental impacts. To check its feasibility the project is then evaluated with the help of matrix method.
Keywords: EIA; Highway